Dramatisk teologi – en introduktion af Raymund Schwager - Thusgård, Esben (Dansk Teologisk Tidsskrift, 2009)
This article introduces the Swiss/Austrian catholic theologian Raymund Schwager (1935-2004) to a Danish audience. It is argued that Schwager’s dramatic theology offers a coherent model for interpreting the paradoxes in Christian faith. How can God be described as both constructive and deconstructive, as both merciful and full of anger? Combining Hans Urs von Balthasar’s conception of drama and René Girard’s theory of mimetic desire and scapegoating, Schwager formulates a theology, where the vertical aspects of reconciliation do not overshadow the horizontal aspects, and vice versa. The action of God in Christ meets human reaction in a balanced way. The drama contains five acts: 1. Jesus proclaims the Kingdom of God; 2. The rejection of Jesus’ preaching; 3. The judgment of Jesus and his crucifixion; 4. Resurrection as the reaction of the Father; 5. The new gathering. The perspective, provided by the drama, makes it possible to integrate themes, which otherwise seem without any relation, for in the drama, as well in our lives, everything is interrelated and interdependent. A dramatic view on the revelation thus clarifies how action is succeeded by reaction: God speaks and human beings respond.